The Intersection of NGF/TrkA Signaling and Amyloid Precursor Protein Processing in Alzheimer’s Disease Neuropathology - Canu, Nadia (Int J Mol Sci, 2017)
Dysfunction of nerve growth factor (NGF) and its high-affinity Tropomyosin receptor kinase A (TrkA) receptor has been suggested to contribute to the selective degeneration of basal forebrain cholinergic neurons (BFCN) associated with the progressive cognitive decline in Alzheimer's disease (AD). The aim of this review is to describe our progress in elucidating the molecular mechanisms underlying the dynamic interplay between NGF/TrkA signaling and amyloid precursor protein (APP) metabolism within the context of AD neuropathology. This is mainly based on the finding that TrkA receptor binding to APP depends on a minimal stretch of ~20 amino acids located in the juxtamembrane/extracellular domain of APP that carries the α- and β-secretase cleavage sites. Here, we provide evidence that: (i) NGF could be one of the “routing” proteins responsible for modulating the metabolism of APP from amyloidogenic towards non-amyloidogenic processing via binding to the TrkA receptor; (ii) the loss of NGF/TrkA signaling could be linked to sporadic AD contributing to the classical hallmarks of the neuropathology, such as synaptic loss, β-amyloid peptide (Aβ) deposition and tau abnormalities. These findings will hopefully help to design therapeutic strategies for AD treatment aimed at preserving cholinergic function and anti-amyloidogenic activity of the physiological NGF/TrkA pathway in the septo-hippocampal system.